Antibacterial enamel layer of water storage container, preparation method and application
By combining modified nano-silica and zeolite molecular sieve heterogeneous bonding and thermally induced phase change complex, the problem of calcium ion precipitation is solved, achieving efficient calcium ion capture and scale inhibition in water storage containers, extending equipment life and avoiding the vicious cycle of strong acid cleaning.
Patent Information
- Application Number
- CN202511265262.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-05
- Publication Date
- 2025-11-18
AI Technical Summary
Existing enamel coatings cannot effectively prevent calcium ion precipitation, leading to scale buildup inside water storage containers, reducing equipment efficiency and lifespan. Furthermore, strong acid cleaning can corrode the enamel surface, creating a vicious cycle.
A Si-O-Zr heterogeneous bonding interface is formed by modifying nano-silica and modified zeolite molecular sieves. Combined with a thermally induced phase change complex, a three-dimensional calcium ion transport channel is constructed through electrostatic adsorption of phosphotungstic acid anion clusters and chelation of phosphonic acid groups. This dynamically maintains the pore patency of the zeolite channels and blocks the growth of calcium carbonate crystals.
It achieves long-term and efficient capture of calcium ions, avoids scale accumulation, improves equipment efficiency and lifespan, and avoids damage to the glaze caused by strong acid cleaning.
Smart Images

Figure CN120965108A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of enamel layer, and particularly relates to an antibacterial enamel layer of a water storage container, a preparation method and application. BACKGROUND
[0002] In the industrial water storage container, calcium ion precipitation and scaling is a long-standing and serious problem. Industrial water generally contains a high concentration of calcium ions, which is easy to precipitate and form hard calcium carbonate scale under the conditions of water temperature fluctuation, pH change or evaporation concentration. These scale layers not only greatly reduce the effective volume of the storage tank and the heat exchange efficiency, but also induce serious local corrosion, which leads to a sharp decrease in the service life of the equipment, a sharp increase in energy loss, and frequent high-cost shutdown cleaning and maintenance.
[0003] Although the existing enamel coating can provide an excellent corrosion-resistant barrier, the smooth surface can only delay but cannot prevent the attachment and growth of scale crystals. Ordinary enamel lacks functional groups that actively inhibit calcium ion scaling, and scale layers will still accumulate after long-term use. Eventually, strong acid cleaning is required, and repeated pickling will erode the glaze surface, forming a vicious cycle. Therefore, developing a new type of enamel layer with dual functions of permanent physical barrier and active ion regulation has become an urgent technical requirement in the field of industrial water storage. SUMMARY
[0004] (1) Technical problem to be solved
[0005] The purpose of the present application is to provide an antibacterial enamel layer of a water storage container, a preparation method and application, which solves the problem of calcium precipitation in the industrial water storage container.
[0006] (2) Technical scheme
[0007] To achieve the above-mentioned purpose, on the one hand, the present application provides an antibacterial enamel layer of a water storage container, the raw materials include modified nano-silicon dioxide 15-20 parts, modified zeolite molecular sieve 15-20 parts, thermotropic phase change composite 5-10 parts, cerium oxide nanorod 0.4-0.5 parts, and polyacrylammonium 0.3-0.4 parts by weight.
[0008] The modified nano-silicon dioxide and the modified zeolite molecular sieve form a Si-O-Zr heterojunction interface; the thermotropic phase change composite includes an inner layer and an outer layer, the inner layer includes tetracosane, and the outer layer includes silica with amino groups on the surface.
[0009] Further, it further includes enamel glaze 100 parts, quartz powder 10 parts, clay 6 parts, potassium carbonate 0.2 parts, antibacterial agent 1 part and deionized water 32 parts.
[0010] Further, the antibacterial agent includes silver-loaded zirconium phosphate.
[0011] Furthermore, the preparation method of the modified nano-silica includes the following steps:
[0012] S11. Remove adsorbed water from silica by vacuum drying, disperse it in toluene under nitrogen protection, sonicate for 30 min, add γ-aminopropyltriethoxysilane dropwise, reflux reaction, centrifuge, wash the precipitate with toluene, and vacuum dry to obtain the first compound;
[0013] S12. Disperse the first compound in acetonitrile, add a 0.3 mol / L acetonitrile solution of phosphotungstic acid, stir the reaction at a constant temperature, collect the solid by centrifugation, and wash with 50% ethanol solution until no WO4 is visible in the filtrate. 2- Vacuum drying yields modified nano-silica.
[0014] Furthermore, the preparation method of the modified zeolite molecular sieve includes the following steps:
[0015] S21. After calcining the zeolite at 550℃, place it in an environment with 90% humidity for 24 hours to obtain activated zeolite;
[0016] S22. The activated zeolite is spread in a vacuum reactor, and the tetraethyl zirconate is vaporized and introduced into the reactor for reaction. The unreacted material is purged with nitrogen to obtain the second compound.
[0017] S23. The second compound was dispersed in ethanol, and a 0.5 mol / L ethanol solution of 2-carboxyethylphosphonic acid was added. The pH was adjusted to 4.5, and the reaction was refluxed to obtain the third compound.
[0018] S24. The third compound was washed with 0.1 mol / L EDTA solution and dried with supercritical CO2 to obtain the modified zeolite molecular sieve.
[0019] Furthermore, the preparation method of the thermally induced phase change composite includes the following steps:
[0020] S31. Mix tetracosane and Span-80 and dissolve them by magnetic stirring to obtain an oil phase; mix deionized water and ethanol to obtain an aqueous phase; slowly pour the oil phase into the aqueous phase, emulsify by high-speed shearing, and then homogenize under high pressure to obtain an emulsion;
[0021] S32. Transfer the emulsion to a constant temperature reaction vessel, stir, add a mixture of ethyl silicate / ethanol dropwise, and simultaneously add a mixture of ammonia / ethanol dropwise. Keep the reaction at the temperature to obtain the reaction solution.
[0022] S33. Centrifuge the reaction solution, wash the solid with 50% ethanol solution, disperse the solid in ethanol, add γ-aminopropyltriethoxysilane, reflux the reaction, centrifuge and wash until neutral, and vacuum dry to obtain the thermally induced phase change complex.
[0023] Furthermore, the volume ratio of ethanol to water in the 50% ethanol solution is 1:1.
[0024] Furthermore, the volume ratio of ethyl silicate to ethanol in the ethyl silicate / ethanol mixture is 1:4; and the volume ratio of ammonia to ethanol in the ammonia / ethanol mixture is 1:9.
[0025] Based on the same inventive concept, in a second aspect, the present invention also provides a method for preparing an antibacterial enamel layer for a water storage container, applicable to the preparation of the antibacterial enamel layer of the water storage container, the preparation method comprising:
[0026] S41. Add ammonium polyacrylate to deionized water and stir. Then add modified nano-silica and cerium oxide nanorods in sequence and disperse at high speed. Then add modified zeolite molecular sieve and disperse. Add thermally induced phase change complex and disperse to obtain a dispersion.
[0027] S42. Enamel glaze, quartz powder, clay and potassium carbonate are put into a V-type mixer for dry mixing, passed through a 200-mesh sieve, then a dispersion liquid is added, ball milling is performed, an antibacterial agent is added, and the mixture is allowed to stand and age to obtain a glaze slurry.
[0028] S43. The glaze slurry is electrostatically sprayed onto the pretreated substrate, pre-baked and dehydrated at 80°C, fired at a stepped temperature, and finally rapidly cooled to obtain an antibacterial enamel layer for a water storage container.
[0029] Based on the same inventive concept, in a third aspect, the present invention also provides an application of an antibacterial enamel layer for a water storage container, wherein the antibacterial enamel layer for the water storage container is used as a coating for the inner liner of an industrial water storage container.
[0030] Two modified substances were added to the antibacterial enamel layer to achieve dual-site calcium ion capture. Modified nano-silica forms a P←N coordination bond with phosphorus atoms in phosphotungstic acid through the lone pair electrons on the amino groups, grafting and fixing phosphotungstic acid onto the surface. The negatively charged phosphotungstic acid anion clusters efficiently adsorb calcium ions through electrostatic interactions, achieving one-site capture of calcium ions. The Keggin structure of phosphotungstic acid severely disrupts the normal growth of calcium carbonate crystals. The modified zeolite molecular sieve contains zirconium phosphonate structures within its pores, where calcium ions are chelated by phosphonate groups (-PO32-) via PO-Ca bonds, achieving the other-site capture of calcium ions. Calcium ion capture in modified nano-silica relies on electrostatic adsorption, a relatively weak and reversible physical bond; calcium ion capture in modified zeolite molecular sieve relies on chemical chelation of phosphonate groups, a stronger and more stable bond. During the enamel firing process, modified nano-silica reacts with modified zeolite molecular sieves to form a Si-O-Zr heterobonded interface, constructing a three-dimensional calcium ion transport channel. This transfers calcium ions captured on the modified nano-silica side to the modified zeolite molecular sieve side. Once the phosphotungstic acid sites on the modified nano-silica side are vacated, they can continue to capture calcium ions in the solution, thus greatly improving the efficiency and durability of the entire system and preventing failure due to adsorption saturation on the silica side. Meanwhile, the modified zeolite molecular sieve, with its large specific surface area and strong chelating ability, becomes the final reservoir for calcium ions, firmly locking them within its pores.
[0031] During the enamel firing process, the molten glaze can clog the channels of the modified zeolite molecular sieve. The tecosane in the inner layer of the thermo-induced phase change composite dynamically maintains the patency of these channels. During the 80℃ pre-drying and dehydration stage, the tecosane absorbs heat and melts into a liquid state, expanding in volume and generating sufficient capillary pressure to actively expel it from the narrow channels of the zeolite molecular sieve. This expulsion process also carries away glaze melt precursors and moisture that could potentially clog the channels, thus clearing the channels before the glaze completely melts and effectively preventing permanent blockage caused by melt penetration. During firing, the amino groups on the outer silica surface form strong coordination bonds with the zirconium ions at the zirconium phosphonate sites of the modified zeolite molecular sieve, thereby fixing the thermo-induced phase change composite to the outer surface of the zeolite and preventing it from drifting off in the glaze slurry or during heating. After calcination and cooling to the operating temperature (e.g., 37°C), tetracosane re-solidifies, shrinking in volume. This creates nanoscale gaps between itself and the inner walls of the pores. These gaps allow calcium ions to move freely but prevent the formation of larger calcium carbonate crystal nuclei, physically blocking the path of crystal growth. The thermo-induced phase change composite ensures that the modified zeolite molecular sieve's large specific surface area and ion exchange capacity are fully preserved after calcination, laying a solid foundation for its long-term, efficient performance of its core functions of chelating calcium ions and inhibiting precipitation.
[0032] (3) Beneficial effects
[0033] Compared with the prior art, the beneficial effects of the present invention are:
[0034] 1. This invention achieves dual-site calcium ion capture by electrostatic adsorption of calcium ions by the phosphotungstic acid anion clusters of modified nano-silica and chelation by phosphonic acid groups within the pores of modified zeolite molecular sieve via PO-Ca bonds. Furthermore, the two modified materials form a Si-O-Zr heterogeneous bonding interface, constructing a three-dimensional calcium ion transport channel to transfer calcium ions captured on the modified nano-silica side to the modified zeolite molecular sieve side.
[0035] 2. This invention dynamically maintains the patency of zeolite channels through a thermally induced phase change composite. During the pre-drying and dehydration stage at 80°C, the inner layer of tetracosane melts into a liquid state, expands in volume, and actively exits from the pores of the zeolite molecular sieve, simultaneously carrying away glaze melt precursors and moisture that could potentially clog the channels. After firing and cooling, it re-solidifies into a solid state, shrinks in volume, and retains the gaps in the zeolite molecular sieve channels, allowing calcium ions to freely pass through. Attached Figure Description
[0036] Figure 1 This is a flowchart illustrating the preparation process of an antibacterial enamel layer for a water storage container. Detailed Implementation
[0037] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention; that is, the described embodiments are merely some embodiments of the invention, not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without inventive effort are within the scope of protection of this invention.
[0038] Example 1: This example discloses an antibacterial enamel layer for a water storage container. The raw materials, by weight, include 18 parts of modified nano-silica, 15 parts of modified zeolite molecular sieve, 8 parts of thermally induced phase change composite, 0.5 parts of cerium oxide nanorods, and 0.3 parts of ammonium polyacrylate.
[0039] The modified nano-silica forms a Si-O-Zr heterogeneous bonding interface with the modified zeolite molecular sieve; the thermally induced phase change composite includes an inner layer and an outer layer, the inner layer including tetracosane and the outer layer including silica with amino groups on the surface.
[0040] It also includes 100 parts enamel glaze, 10 parts quartz powder, 6 parts clay, 0.2 parts potassium carbonate, 1 part antibacterial agent, and 32 parts deionized water.
[0041] The antibacterial agent includes silver-loaded zirconium phosphate.
[0042] The method for preparing the modified nano-silica includes the following steps:
[0043] S11. 100g of silica was dried under vacuum at 120℃ for 2h to remove adsorbed water, dispersed in 400ml of toluene under nitrogen protection, sonicated for 30min, 25ml of γ-aminopropyltriethoxysilane was added dropwise, refluxed at 75℃ for 6h, centrifuged (8000rpm), the precipitate was washed 3 times with toluene, and dried under vacuum at 60℃ to obtain the first compound.
[0044] S12. Disperse the first compound in 200 ml of acetonitrile, add 100 ml of acetonitrile solution containing 0.3 mol / L phosphotungstic acid, stir at 45 °C for 12 h, collect the solid by centrifugation, and wash with 50% ethanol solution until no WO4 is visible in the filtrate. 2- Modified nano-silica was obtained by vacuum drying at 60℃.
[0045] The preparation method of the modified zeolite molecular sieve includes the following steps:
[0046] S21. After calcining 100g of zeolite at 550℃ for 4h to remove the template agent, place it in an environment with 90% humidity for 24h to hydroxylate the surface and obtain activated zeolite.
[0047] S22. The activated zeolite was spread in a vacuum reactor (pressure <10Pa), 40ml of tetraethyl zirconate was heated to 80℃ and vaporized, and then introduced into the reactor. The reaction was carried out at 150℃ for 3h. The unreacted material was purged with nitrogen to obtain the second compound.
[0048] S23. The second compound was dispersed in 300 ml of ethanol, and a 0.5 mol / L ethanol solution of 2-carboxyethylphosphonic acid was added. The pH was adjusted to 4.5 with acetic acid, and the mixture was refluxed at 80 °C for 8 h to obtain the third compound.
[0049] S24. The third compound was washed with 0.1 mol / L EDTA solution to remove free zirconium from the surface, and dried with supercritical CO2 (40℃, 20 MPa) to obtain the modified zeolite molecular sieve.
[0050] The preparation method of the thermally induced phase change composite includes the following steps:
[0051] S31. Mix 80g of tetracosane and 1.6g of Span-80 and stir magnetically to dissolve to obtain the oil phase; mix 200ml of deionized water and 50ml of ethanol to obtain the aqueous phase; slowly pour the oil phase into the aqueous phase, emulsify at 2000rpm for 10min, and then homogenize under high pressure (cycle 5 times at 30MPa) to obtain the emulsion.
[0052] S32. Transfer the emulsion to a constant temperature reactor (55℃), stir at 300 rpm, add a mixture of ethyl silicate / ethanol dropwise, and simultaneously add a mixture of ammonia / ethanol dropwise. Keep the reaction at this temperature for 3 hours to obtain the reaction solution.
[0053] S33. Centrifuge the reaction solution (4000 rpm / 10 min), wash the solid three times with 50% ethanol solution, disperse the solid in 200 ml of ethanol, add 4 ml of γ-aminopropyltriethoxysilane, reflux at 60 °C for 4 h, centrifuge and wash until neutral (pH = 7.0), and vacuum dry at 40 °C for 12 h to obtain the thermally induced phase change complex.
[0054] The volume ratio of ethanol to water in the 50% ethanol solution is 1:1.
[0055] The volume ratio of ethyl silicate to ethanol in the ethyl silicate / ethanol mixture is 1:4; the volume ratio of ammonia to ethanol in the ammonia / ethanol mixture is 1:9.
[0056] Based on the same inventive concept, in a second aspect, the present invention also provides a method for preparing an antibacterial enamel layer for a water storage container, applicable to the preparation of the antibacterial enamel layer of the water storage container, the preparation method comprising:
[0057] S41. Add ammonium polyacrylate to deionized water, stir at 500 rpm for 5 min, add modified nano silica and cerium oxide nanorods in sequence, disperse at 2000 rpm for 30 min, then add modified zeolite molecular sieve, disperse at 1200 rpm for 15 min, reduce the speed to 800 rpm and slowly add thermally induced phase change composite, disperse for 10 min to obtain dispersion.
[0058] S42. Add enamel glaze, quartz powder, clay, and potassium carbonate to a V-type mixer and dry mix for 1 hour. After passing through a 200-mesh sieve, add dispersion liquid, ball mill for 4 hours, add antibacterial agent, and let stand and age for 24 hours to obtain glaze slurry.
[0059] S43. The glaze slurry is electrostatically sprayed onto the pretreated substrate, pre-baked at 80℃ for 30 min to dehydrate, and then fired in a stepped temperature control manner: the temperature is increased from 80℃ to 300℃ at a rate of 2℃ / min and held for 60 min; then increased from 300℃ to 450℃ at a rate of 1.5℃ / min and held for 30 min; then increased from 450℃ to 520℃ at a rate of 1℃ / min and held for 20 min; finally, it is rapidly cooled (reduced to 100℃ within 5 min) to obtain an antibacterial enamel layer for a water storage container. The preparation process is as follows: Figure 1 As shown.
[0060] Based on the same inventive concept, in a third aspect, the present invention also provides an application of an antibacterial enamel layer for a water storage container, wherein the antibacterial enamel layer for the water storage container is used as a coating for the inner liner of an industrial water storage container.
[0061] Example 2: This example discloses an antibacterial enamel layer for a water storage container. The raw materials, by weight, include 15 parts modified nano-silica, 15 parts modified zeolite molecular sieve, 5 parts thermally induced phase change composite, 0.4 parts cerium oxide nanorods, and 0.3 parts ammonium polyacrylate.
[0062] The other components and preparation methods are the same as in Example 1.
[0063] Example 3: This example discloses an antibacterial enamel layer for a water storage container. The raw materials, by weight, include 20 parts modified nano-silica, 20 parts modified zeolite molecular sieve, 10 parts thermally induced phase change composite, 0.5 parts cerium oxide nanorods, and 0.4 parts ammonium polyacrylate.
[0064] The other components and preparation methods are the same as in Example 1.
[0065] Example 4: This example discloses an antibacterial enamel layer for a water storage container. The raw materials, by weight, include 17.5 parts modified nano-silica, 17.5 parts modified zeolite molecular sieve, 7.5 parts thermally induced phase change composite, 0.45 parts cerium oxide nanorods, and 0.35 parts ammonium polyacrylate.
[0066] The other components and preparation methods are the same as in Example 1.
[0067] Comparative Example 1: Based on Example 1, but unlike Example 1, no amino groups are introduced into the modified nano silica in this comparative example.
[0068] The method for preparing the modified nano-silica includes the following steps:
[0069] S11. Disperse 100g of silica in 200ml of acetonitrile, add 100ml of acetonitrile solution containing 0.3mol / L phosphotungstic acid, stir at 45℃ for 12h, collect the solid by centrifugation, and wash with 50% ethanol solution until no WO4 is visible in the filtrate. 2- Modified nano-silica was obtained by vacuum drying at 60℃.
[0070] The other components and preparation methods are the same as in Example 1.
[0071] Comparative Example 2: Based on Example 1, but unlike Example 1, the modified nano-silica in this comparative example is not grafted with phosphotungstic acid.
[0072] The method for preparing the modified nano-silica includes the following steps:
[0073] S11. 100g of silica was vacuum dried at 120℃ for 2h to remove adsorbed water, dispersed in 400ml of toluene under nitrogen protection, sonicated for 30min, 25ml of γ-aminopropyltriethoxysilane was added dropwise, refluxed at 75℃ for 6h, centrifuged (8000rpm), the precipitate was washed 3 times with toluene, and vacuum dried at 60℃ to obtain modified nano silica.
[0074] The other components and preparation methods are the same as in Example 1.
[0075] Comparative Example 3: Based on Example 1, but unlike Example 1, the modified zeolite molecular sieve in this comparative example is not grafted with zirconium hydroxyl groups.
[0076] The preparation method of the modified zeolite molecular sieve includes the following steps:
[0077] S21. After calcining 100g of zeolite at 550℃ for 4h to remove the template agent, place it in an environment with 90% humidity for 24h to hydroxylate the surface and obtain activated zeolite.
[0078] S22. Disperse the activated zeolite in 300 ml of ethanol, add a 0.5 mol / L ethanol solution of 2-carboxyethylphosphonic acid, adjust the pH to 4.5 with acetic acid, and reflux at 80 °C for 8 h to obtain the second compound;
[0079] S23. The second compound was washed with 0.1 mol / L EDTA solution and dried with supercritical CO2 (40℃, 20 MPa) to obtain the modified zeolite molecular sieve.
[0080] The other components and preparation methods are the same as in Example 1.
[0081] Comparative Example 4: Based on Example 1, but unlike Example 1, the modified zeolite molecular sieve in this comparative example is not grafted with phosphonic acid groups.
[0082] The preparation method of the modified zeolite molecular sieve includes the following steps:
[0083] S21. After calcining 100g of zeolite at 550℃ for 4h to remove the template agent, place it in an environment with 90% humidity for 24h to hydroxylate the surface and obtain activated zeolite.
[0084] S22. The activated zeolite was spread in a vacuum reactor (pressure <10Pa), 40ml of tetraethyl zirconate was heated to 80℃ and vaporized, and then introduced into the reactor. The reaction was carried out at 150℃ for 3h. The unreacted material was purged with nitrogen to obtain the second compound.
[0085] S23. The second compound was washed with 0.1 mol / L EDTA solution and dried with supercritical CO2 (40℃, 20 MPa) to obtain the modified zeolite molecular sieve.
[0086] The other components and preparation methods are the same as in Example 1.
[0087] Comparative Example 5: Based on Example 1, except that this comparative example does not include modified nano-silica.
[0088] Comparative Example 6: Based on Example 1, except that this comparative example does not include modified zeolite molecular sieves.
[0089] Comparative Example 7: Based on Example 1, except that this comparative example does not include modified nano-silica and modified zeolite molecular sieve.
[0090] Comparative Example 8: Based on Example 1, but unlike Example 1, this comparative example does not include the thermally induced phase change complex.
[0091] Experimental Example 1: The antibacterial enamel layer samples (50mm × 50mm) obtained from Examples 1-4 and Comparative Examples 1-8 were completely immersed in 100mL of simulated solution (containing Ca2+). + The sample (concentration of 500 mg / L, total alkalinity of 300 mg / L) was placed in a constant temperature shaking water bath at 60℃ and samples were taken periodically (0, 7, 14, 21, 28 days) for testing. The test indicators included surface deposition amount, surface characteristics, and calcium ion adsorption rate. The results are shown in Table 1.
[0092] Table 1. Detection of calcium ion precipitation inhibition by enamel layer
[0093]
[0094]
[0095] Based on the results in Table 1, compared with Comparative Examples 1 and 2, Example 1 shows that the modified nano-silica, whether lacking amino groups or having amino groups but lacking phosphotungstic acid, cannot actively capture calcium ions. Compared with Comparative Examples 3 and 4, Example 1 shows that the modified zeolite molecular sieve, whether lacking zirconium hydroxyl groups or having zirconium hydroxyl groups but lacking phosphotungstic acid groups, has a low adsorption capacity. Compared with Comparative Example 5, Example 1 shows that relying solely on the modified zeolite molecular sieve to chelate calcium ions has limited capacity and lacks phosphotungstic acid to inhibit crystal growth, leading to later blockage and failure. Compared with Comparative Example 6, Example 1 shows that relying solely on phosphotungstic acid adsorption results in extremely small capacity, rapid saturation and failure, and inability to prevent the formation of large crystal nuclei. Comparative Example 7 shows no ability to inhibit calcium ions, with the most severe precipitation. Compared with Comparative Example 8, Example 1 shows that without a thermally induced phase change complex, the blockage of the modified zeolite molecular sieve channels leads to a significant decline in system performance.
[0096] Test Example 2: The antibacterial enamel layer samples obtained in Examples 1-4 were subjected to basic performance tests, including abrasion resistance (according to ASTM D4060), acid and alkali resistance (refer to ISO 28706), and antibacterial properties (refer to ISO 22196); the results are shown in Table 2.
[0097] Table 2 Basic Performance Testing of Enamel Layer
[0098]
[0099]
[0100] Finally, it should be noted that although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. An antibacterial enamel layer for a water storage container, characterized in that, The raw materials, by weight, include 15-20 parts of modified nano-silica, 15-20 parts of modified zeolite molecular sieve, 5-10 parts of thermally induced phase change composite, 0.4-0.5 parts of cerium oxide nanorods, and 0.3-0.4 parts of ammonium polyacrylate. The modified nano-silica forms a Si-O-Zr heterogeneous bonding interface with the modified zeolite molecular sieve; the thermally induced phase change composite includes an inner layer and an outer layer, the inner layer including tetracosane and the outer layer including silica with amino groups on the surface.
2. The antibacterial enamel layer of a water storage container according to claim 1, characterized in that, It also includes 100 parts enamel glaze, 10 parts quartz powder, 6 parts clay, 0.2 parts potassium carbonate, 1 part antibacterial agent, and 32 parts deionized water.
3. The antibacterial enamel layer of a water storage container according to claim 2, characterized in that, The antibacterial agent includes silver-loaded zirconium phosphate.
4. The antibacterial enamel layer of a water storage container according to claim 1, characterized in that, The method for preparing the modified nano-silica includes the following steps: S11. Remove adsorbed water from silica by vacuum drying, disperse it in toluene under nitrogen protection, sonicate for 30 min, add γ-aminopropyltriethoxysilane dropwise, reflux reaction, centrifuge, wash the precipitate with toluene, and vacuum dry to obtain the first compound; S12. Disperse the first compound in acetonitrile, add a 0.3 mol / L acetonitrile solution of phosphotungstic acid, stir the reaction at a constant temperature, collect the solid by centrifugation, and wash with 50% ethanol solution until no WO4 is visible in the filtrate. 2- Vacuum drying yields modified nano-silica.
5. The antibacterial enamel layer of a water storage container according to claim 1, characterized in that, The preparation method of the modified zeolite molecular sieve includes the following steps: S21. After calcining the zeolite at 550℃, place it in an environment with 90% humidity for 24 hours to obtain activated zeolite; S22. The activated zeolite is spread in a vacuum reactor, and the tetraethyl zirconate is vaporized and introduced into the reactor for reaction. The unreacted material is purged with nitrogen to obtain the second compound. S23. The second compound was dispersed in ethanol, and a 0.5 mol / L ethanol solution of 2-carboxyethylphosphonic acid was added. The pH was adjusted to 4.5, and the reaction was refluxed to obtain the third compound. S24. The third compound was washed with 0.1 mol / L EDTA solution and dried with supercritical CO2 to obtain the modified zeolite molecular sieve.
6. The antibacterial enamel layer of a water storage container according to claim 1, characterized in that, The preparation method of the thermally induced phase change composite includes the following steps: S31. Mix tetracosane and Span-80 and dissolve them by magnetic stirring to obtain an oil phase; mix deionized water and ethanol to obtain an aqueous phase; slowly pour the oil phase into the aqueous phase, emulsify by high-speed shearing, and then homogenize under high pressure to obtain an emulsion; S32. Transfer the emulsion to a constant temperature reaction vessel, stir, add a mixture of ethyl silicate / ethanol dropwise, and simultaneously add a mixture of ammonia / ethanol dropwise. Keep the reaction at the temperature to obtain the reaction solution. S33. Centrifuge the reaction solution, wash the solid with 50% ethanol solution, disperse the solid in ethanol, add γ-aminopropyltriethoxysilane, reflux the reaction, centrifuge and wash until neutral, and vacuum dry to obtain the thermally induced phase change complex.
7. The antibacterial enamel layer of a water storage container according to claims 4 and 6, characterized in that, The volume ratio of ethanol to water in the 50% ethanol solution is 1:
1.
8. The antibacterial enamel layer of a water storage container according to claim 6, characterized in that, The volume ratio of ethyl silicate to ethanol in the ethyl silicate / ethanol mixture is 1:4; the volume ratio of ammonia to ethanol in the ammonia / ethanol mixture is 1:
9.
9. A method for preparing an antibacterial enamel layer for a water storage container, applied to the preparation of an antibacterial enamel layer for a water storage container as described in any one of claims 1 to 8, characterized in that, The preparation method includes: S41. Add ammonium polyacrylate to deionized water and stir. Then add modified nano-silica and cerium oxide nanorods in sequence and disperse at high speed. Then add modified zeolite molecular sieve and disperse. Add thermally induced phase change complex and disperse to obtain a dispersion. S42. Enamel glaze, quartz powder, clay and potassium carbonate are put into a V-type mixer for dry mixing, passed through a 200-mesh sieve, then a dispersion liquid is added, ball milling is performed, an antibacterial agent is added, and the mixture is allowed to stand and age to obtain a glaze slurry. S43. The glaze slurry is electrostatically sprayed onto the pretreated substrate, pre-baked and dehydrated at 80°C, fired at a stepped temperature, and finally rapidly cooled to obtain an antibacterial enamel layer for a water storage container.
10. The application of an antibacterial enamel layer to a water storage container, characterized in that, The antibacterial enamel layer of the water storage container according to any one of claims 1-8 is used as the coating for the inner liner of an industrial water storage container.